Reflex Postural Control of Patients with Cerebral Palsy for Odontological Assistance - Aguiar, Sandra Maria Herondina Coelho Ávila de; Alves Rezende, Maria Cristina Rosifini (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Cerebral palsy (CP) describes a group of permanent disorders of the development of movement and posture, causing activity limitation, that are attributed to non-progressive disturbances that occurred in the developing fetal or infant brain.A child with cerebral palsy may have impairments in motor control, which contributes to loss of functional abilities in posture and mobility. The severity of the impairment on the neuromuscular system determines the variations of functional mobility in children with cerebral palsy. The control of the patient, during the dental treatment, is of fundamental importance because these patients present some pathological reflexes which interfere in the odontological assistance. Keywords: Cerebral Palsy; Postural Balance; Dental Care.